The Palestinian labor market over the last three decades - Sameh Hallaq (Levy Economics Institute of Bard College, 2020)
This paper consists of three economic literature review essays that survey the Palestinian labor market during the last three decades. The first essay examines the economic return to schooling since 1981 until the recent period, taking into consideration the major shocks that the Palestinian economy experienced, such as the First and Second Palestinian Intifadas (1987-93 and 2000-5), respectively, and the establishment of the Palestinian National Authority in 1993. A special focus is laid on overcoming the potential endogeneity arising from the schooling coefficient. The second essay discusses the economic costs of several conflict measures (e.g., time and geographical variation in fatalities and other conflict incidents, days under curfews, checkpoints, movement restrictions, and substitution of foreigner workers for Palestinian labor) on the labor market and human capital. Earnings and unemployment are the main labor market indicators, while the human capital impact was assessed by educational attainment. The third essay sheds light on the wage differential in the Palestinian labor market due to geographical and employment sector factors.
Keywords: E24; J31; J24; J40; J61; 330; Returns to Schooling; Israeli-Palestinian Conflict; Wage Differential